2012
DOI: 10.1590/s1980-65232012000100009
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic bonding to porcelain surfaces: in vitro shear bond strength

Abstract: Purpose: To evaluate in vitro the shear bond strength of orthodontic accessories to porcelain, under different porcelain surface treatment protocols, and the resultant failure pattern after debonding. Methods: The sample consisted of 80 feldspathic porcelain discs, divided into 4 groups: Group 1-37% Phosphoric acid etching; Group 2-10% fluorhydric acid; Group 3-37% Phosphoric acid and silane application; Group 4-10% fluorhydric acid and silane application. The samples were submitted to the shear bond strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In the present research, when the same group was stored in water for 150 days, the shear bond strength was reduced to 10.24 MPa, less than half the original value, but still within the bond strength considered clinically acceptable by the literature. In recent literature, it has been affirmed that the use of 37% phosphoric acid associated with silane as porcelain surface treatment may promote an adequate bond strength of orthodontic bonding, suggesting that its use would be more adequate than that of fluorhydric acid, since it offers lower risk to oral tissues (less toxicity), in addition to causing a lower number of irreversible failures in the restorative surface (cracks and fractures in porcelain) [15]. Nevertheless, in the present research it was observed that this bonding protocol, in wet conditions for 150 days, did not have favorable results, since the bond strength required for resisting the forces applied during an orthodontic treatment was not attained, being short of the desired value.…”
Section: Discussionmentioning
confidence: 99%
“…In the present research, when the same group was stored in water for 150 days, the shear bond strength was reduced to 10.24 MPa, less than half the original value, but still within the bond strength considered clinically acceptable by the literature. In recent literature, it has been affirmed that the use of 37% phosphoric acid associated with silane as porcelain surface treatment may promote an adequate bond strength of orthodontic bonding, suggesting that its use would be more adequate than that of fluorhydric acid, since it offers lower risk to oral tissues (less toxicity), in addition to causing a lower number of irreversible failures in the restorative surface (cracks and fractures in porcelain) [15]. Nevertheless, in the present research it was observed that this bonding protocol, in wet conditions for 150 days, did not have favorable results, since the bond strength required for resisting the forces applied during an orthodontic treatment was not attained, being short of the desired value.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect ceramic dental restorations are considered the materials of choice in dentistry to replace lost or damaged teeth owing to their esthetic advantages, excellent mechanical properties, and biocompatibility. [ 1 2 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, bond strength should allow the brackets to come off at the end of treatment without damaging the restoration surface, maintaining its initial structure. [ 3 4 6 10 11 ] In vitro studies have shown that bonding adhesives must be able to withstand loads of 5.9 to 7.8 MPa to be considered clinically suitable for orthodontic purposes. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Roughness may be achieved by mechanical means using diamond tips or airborne particle abrasion with aluminum oxide particles 1,6 . However, the literature has demonstrated crack propagation within the ceramic, and consequent weakening of the part, making it unfeasible to use this form of roughening 7 . Furthermore, treatment with hydrofluoric acid, saline application or even a combination of these treatments has also been indicated 5,7,8 .…”
Section: Introductionmentioning
confidence: 99%